A atuação de educadores em movimentos sociais: uma possibilidade de construção de novas práticas político-participativas para a educação cidadã - Cordeiro, Salete de Fátima Noro (2002)
The research came from our anxiety in finding out the knowledge built by educators in the extent of participation and militancy in social movements, here represented by Christian Educators Movement, Niger Movement, and Resident Association. Glimpsing the possibility of contributing from their participation in these situations to the construction of a participant pedagogical practice to the public school teachers, we emphasized the following objectives: identifying and analyzing the knowledge produced by educators in their actuation in these situations of participation; analyzing the kinds of militancy that they carry out in the movements and verifying the causes that conducted them to look for these places of participation. In order to achieve this thematic, we were based on authors such as Antônio Nóvoa, Francisco Imbernón, Paulo Freire, Joe L. Kincheloe, Henry A. Giroux, et al. Under the methodological point of view, this research characterized as a qualitative study in which we were worried in selecting meaningful evidences in order to understand the approached problematic. During the period of investigation, we realized that the school impose several barriers such as routine and bureaucracy of its processes not offering the opportunity of educator participation in decisions making. On the other hand, we found educators relief valve in social movements, local where there are movements of relaxing, work, and learning to their lives and profession. As a result, we can mention the coherency established between discourse in the movement and its action in the school or in the classroom; conscience making in taking into account the student everyday as a “back cloth” to his/her planning and the need of participating and implementing projects in schools that have as principles the participation of students and the interaction with the community, searching the formation of citizenship.